Randomised controlled trial on the effectiveness of home-based walking exercise on anxiety, depression and cancer-related symptoms in patients with lung cancer - Hui‐Mei Chen; C-M Tsai; Y-C Wu; K‐C. Lin; Chia‐Chin Lin (2014)
Although exercise has been addressed as an adjuvant treatment for anxiety, depression and cancer-related symptoms, limited studies have evaluated the effectiveness of exercise in patients with lung cancer. We recruited 116 patients from a medical centre in northern Taiwan, and randomly assigned them to either a walking-exercise group (n=58) or a usual-care group (n=58). We conducted a 12-week exercise programme that comprised home-based, moderate-intensity walking for 40 min per day, 3 days per week, and weekly exercise counselling. The outcome measures included the Hospital Anxiety and Depression Scale and the Taiwanese version of the MD Anderson Symptom Inventory. We analysed the effects of the exercise programme on anxiety, depression and cancer-related symptoms by using a generalised estimating equation method. The exercise group patients exhibited significant improvements in their anxiety levels over time (P=0.009 and 0.006 in the third and sixth months, respectively) and depression (P=0.00006 and 0.004 in the third and sixth months, respectively) than did the usual-care group patients. The home-based walking exercise programme is a feasible and effective intervention method for managing anxiety and depression in lung cancer survivors and can be considered as an essential component of lung cancer rehabilitation.